Menangani Krisis Perkembangan Remaja Awal melalui Layanan Konseling di SMP - Dolongseda, Rachel Clarisa; Makanoneng, Lira In; Londo, Fellyzia Anastasya (PT. Giat Konseling Nusantara, 2025)
Early adolescents, particularly junior high school (SMP) students, are in a critical developmental phase marked by biological, psychological, and social changes. This stage often leads to developmental crises related to the search for self-identity, emotional stability, and adjustment to environmental changes. If not properly addressed, these crises may evolve into behavioral problems such as juvenile delinquency, anxiety, and social withdrawal. This article aims to examine the role of counseling services in effectively helping junior high school students overcome early adolescent developmental crises. The research was conducted using a literature review method, collecting and analyzing relevant sources. The results indicate that counseling services in junior high schools are essential as preventive, curative, and personality development tools. The three main forms of counseling services—individual, group, and classroom-based—play a strategic role in addressing students' needs according to their specific issues. Counseling approaches such as nondirective, behavioral, cognitive, and logotherapy have proven effective in helping students understand themselves, change negative behaviors, and find meaning in life amid developmental pressures. Factors such as family, social media, and peer environment greatly influence the dynamics of adolescent crises. Therefore, counseling services must be systematically and professionally designed as an integral part of the junior high school education system to support mental health and the formation of a positive adolescent identity from an early age.